The Dynamics of Parasocial Interaction and Fan Engagement in Community Value Creation - Christian Dwi Tama Putra; Bagas Aji Pratama; I Made Bayu Dirgantara (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In the digital era, parasocial interactions and fan engagement have become important phenomena in marketing because they have the potential to increase consumer participation and business value. This study aims to answer two main questions: how parasocial relationships encourage customer participation in value co-creation, and what marketing mechanisms transform fan engagement into sustainable brand communities. The research was conducted through a systematic literature review in the fields of marketing and consumer behavior, synthesizing findings from various studies related to parasocial interactions and fan engagement. The analysis results show that emotional connectivity is a catalyst for consumer-led marketing activities, including user-generated content, brand advocacy, and community-based innovation. Digitally mediated parasocial relationships can reduce marketing costs while increasing customer lifetime value through organic engagement. This study provides a strategic framework for brand community management, emphasizing the importance of cultivating parasocial relationships to increase loyalty, word-of-mouth promotion, and premium pricing appeal, thereby creating an emotionally connected consumer ecosystem and generating measurable business value.